A review on fog computing: Issues, characteristics, challenges, and potential applications - Das, Resul; Inuwa, Muhammad Muhammad (Elsevier, 2023)
Fog computing is a paradigm that utilizes the advantages of both the cloud and the edge devices providing quality services, reducing latency, providing mobility support, multi-tenancy, and many other functions that support modern computing systems. It is sometimes referred to as fog networking or fogging. This paper reviews and discusses cloud computing, briefly highlighting the implemented paradigms before fog computing. These paradigms include cloud, mobile cloud computing, and mobile edge computing. All the paradigms targeted improving the quality of service between the end devices and the cloud itself. A fog computing Taxonomy is presented based on contemporary fog computing research about security challenges, services issues, operational issues, and data management. The standard for elucidating the taxonomy is built on the functional and vital issues in fog computing. Challenges and potential applications are identified. The review shows that security, privacy, application, and communication challenges are prominent among scholars contributions. Potential applications in fog computing are also identified, including healthcare applications, innovative city applications, and farm applications.
Keywords: Fog computing; Edge computing; Internet of Things (IoT); Cyber security; Security threats